Pro-Fibrotic Macrophage Subtypes: SPP1+ Macrophages as a Key Player and Therapeutic Target in Cardiac Fibrosis? - Moritz Uhlig; Sebastian Billig; Jan Wienhold; David Schumacher (Cells)
Cardiac fibrosis is a major driver of heart failure, a leading cause of morbidity and mortality worldwide. Advances in single-cell transcriptomics have revealed the pivotal role of SPP1+ macrophages in the pathogenesis of cardiac fibrosis, positioning them as critical mediators and promising therapeutic targets. SPP1+ macrophages, characterized by elevated expression of secreted phosphoprotein 1 (SPP1) and often co-expressing Triggering Receptor Expressed on Myeloid Cells 2 (TREM2), localize to fibrotic niches in the heart and other organs. These cells interact with activated fibroblasts and myofibroblasts, driving extracellular matrix remodeling and fibrosis progression. Their differentiation is orchestrated by signals such as CXCL4, GM-CSF, and IL-17A, further emphasizing their regulatory complexity. Therapeutic strategies targeting SPP1+ macrophages have shown encouraging preclinical results. Approaches include silencing Spp1 using antibody–siRNA conjugates and modulating key pathways involved in macrophage differentiation. These interventions have effectively reduced fibrosis and improved cardiac function in animal models. The mechanisms underlying SPP1+ macrophage function in cardiac fibrosis provide a foundation for innovative therapies aimed at mitigating pathological remodeling and improving outcomes in patients with heart failure. This emerging field has significant potential to transform the treatment of fibrotic heart disease.